The Influence of Relationships, Training, and Professionalism on Auditor Competence at Inspektorat Daerah Kota Pangkalpinang - Rizky, Dwi; Ali, Hapzi (Universitas Syiah Kuala, 2024)
This study aims to analyze the Influence of Relationship, Training, and Professionalism on Auditor Competence in Inspektorat Daerah Kota Pangkalpinang. This type of research is Quantitative which is causal (experimental). The population of the study was Auditors of the Inspektorat Daerah Kota Pangkalpinang with a sample of 20 samples selected using the Simple Random Sampling Selection Technique. The data collection technique used a questionnaire in the form of a Likert scale. Data processing in this study used SPSS Software version 29. The results of this study indicate that 1) Relationships do not have a positive and significant effect on Auditor Competence. 2) Training has a positive and significant effect on Auditor Competence. 3) Professionalism has a positive and significant effect on Auditor Competence.